PENERAPAN HUKUM TERHADAP PELAKU PENYEBARAN KONTEN PORNOGRAFI - Rizki, Muhammad; Harahap, Irawan; Pardede, Rudi (LPPM STIH Awang Long, 2025)
Pornography in Indonesia is a serious concern for the government, as the Associated Press once stated that Indonesia could become the next haven for pornography. This is due to the ease with which erotic or sensual images and information can now be downloaded and accessed simply for viewing or enjoyment. Certain individuals have taken advantage of this situation by developing and commercializing pornographic materials. Such content can now be found almost anywhere, with virtually no restrictions on accessing pornographic videos or images. The spread of pornographic content through the internet has become increasingly easy and fast, necessitating firm actions to prevent it. The objective of this study is to analyze the enforcement of the law against individuals who distribute pornographic content under Law No. 44 of 2008 on Pornography (Case Study at the Criminal Investigation Unit of Pekanbaru City Police). Specifically, it aims to examine the obstacles in the implementation of criminal law against the distribution of pornographic content, and to analyze the efforts and solutions to overcome these obstacles under the same law. The research method used is a sociological legal approach. The findings reveal that the enforcement of the law against perpetrators of pornographic content distribution has been carried out by the Criminal Investigation Unit of the Pekanbaru City Police in accordance with the provisions of the Pornography Law and the Law on Electronic Information and Transactions (ITE Law). Legal enforcement involves stages of investigation, inquiry, and case transfer to the prosecution, guided by relevant criminal provisions. However, the enforcement is not yet fully effective, as many cases remain undisclosed or do not proceed to prosecution—particularly those involving distribution through social media and digital applications. The obstacles identified include: difficulties in digital evidence collection due to the use of anonymous accounts and VPNs by perpetrators; limited forensic digital capabilities among law enforcement officers; ambiguous legal norms within the Pornography Law that lead to varied interpretations; and low public awareness regarding the dangers of distributing obscene content. Additional challenges include cultural and psychological barriers that deter victims from reporting, and weak coordination among institutions and digital platform providers in addressing pornographic content. Proposed solutions include: enhancing law enforcement capacity through digital forensic training; harmonizing legal norms to make them clearer and more operational; increasing digital literacy and legal education among the public; and optimizing cooperation between the government and internet service providers. A restorative justice approach can also be considered in certain cases, especially those involving children or adolescents, to ensure that law enforcement remains humane. Furthermore, the establishment of a dedicated cybercrime unit to professionally and sustainably handle digital pornography cases is essential.